Spline Based Channel Estimation for STBC-SM Systems over Fast-Varying Rician Fading Channels - Doğan, Hakan; Panayırcı, Erdal; ACAR, YUSUF (IEEE, 345 E 47Th St, New York, Ny 10017 USA, 2015)
In the STBC-SM systems, the information is carried both by STBC symbols and indices of the transmit antennas from which these symbols are transmitted. Channel estimation is a critical process at the receiver during the coherent detection of the transmitted STBC symbols and indices of the transmit antennas. In this paper, a spline interpolation and pilot symbols based channel estimation has been proposed for the space-time block coded spatial modulation (STBC-SM) systems to track the channel variations in the presence of Rician fading channels. The estimation of channel at pilot durations is done by least squares (LS) method and then the spline based channel interpolation is performed. It has been shown via computer simulations that the proposed spline based channel estimation channel estimation outperforms the piecewise linear interpolation (PLI) and the nearest neighbor interpolation (NNI) based channel estimations.
Keywords: Spatial Modulation; MIMO; STBC; Pilot Symbol Assisted Channel Estimation; Time Varying Rician Fading Channels